ПРОБЛЕМИ УТИЛІЗАЦІЇ ЗОЛИ ВІД КОТЕЛЬНИХ НА БІОМАСІ В УКРАЇНІ - Kramar, V.G. (Institute of Engineering Thermophysics of NAS of Ukraine, 2021)
As  result of the study, it was estimated that in 2019 in Ukraine  the annual biomass ash formation to be utilized, amounted to 132 thousand tons, and in the future, subject to the goals of bioenergy development, it may increase almost 10 times until 2050. The main way to treat biomass ash in Ukraine is to bury it in landfills, partly use in landfills as an insulating material, and partly as fertilizer, mainly in homesteads. In Ukraine, the widespread use of biomass ash is limited by the lack of legal requirements for its utilization, absence of technical requirements for its use in the construction industry, complex procedure of state registration of pesticides and agrochemicals, which puts biomass ash in unequal competitition with the mineral fertilizers. Also, a certain barrier to the use of biomass ash as a fertilizer is its physical and chemical characteristics, which require special methods of its application. The increase in useful utilization of ash requires field research of its effectiveness as a fertilizer, development of different types of fertilizers based on biomass ash for different types of soils and crops and methods of their use with proven efficiency, development of the most efficient utilization methods of the ash, which does not meet the requirements of its use in agriculture, in other industries.